(untitled) (Fiep Bulletin - online, 2014)
The aims of this study were: compare the blood lactate concentrations and times of swimming tests of efforts in two different training periods (general endurance preparatory and specific endurance preparatory), and verify the sTNF-R1 concentrations after acute effort in specific endurance preparatory period. This study was approved by Ethical Committee for Studies with Humans by UFMG. Fifteen swimmers participated and were informed of the risks and purposes of this study before their signed the consent. The Vitesse protocol was utilized to determinate lactate concentration, the blood collects were in both training periods, and the analysis was by Accusport Lactate Meter. The blood samples collected to verify sTNF-R1 concentrations were just in preparatory of specific endurance training period and this analysis were by ELISA. The lactate values of specific endurance were higher than the general endurance values (p=0,0002). The times of swimming tests of efforts in general endurance were higher than specific endurance (p=0,0043). The average of sTNFR1 concentrations after acute effort was higher than basal values. The conclusion is that were alterations in athletes conditionings and increase in inflammatory response after acute effort, in the training periods that were evaluated.